Selective estrogen receptor modulator BC-1 activates antioxidant signaling pathway in vitro via formation of reactive metabolites - Yu Bo-lan; Mai Zi-xin; Liu Xu-xiang; Huang Zhao-feng (Acta Pharmacologica Sinica, 2016)
Bo-lan YU1, *, Zi-xin MAI1, Xu-xiang LIU2, Zhao-feng HUANG2, * 1Key Laboratory of Reproduction and Genetics of Guangdong Higher Education Institute, Third Affiliated Hospital of Guangzhou Medical University, Guangzhou 510150, China; 2Institute of Human Virology, Zhongshan School of Medicine, Sun Yat-sen University, Guangzhou 510080, China Aim: Chickpea (Cicer arietinum L) is a traditional Uighur herb. In this study we investigated the estrogenic activities of the isoflavones extracted from chickpea sprouts (ICS) in ovariectomized rats. Methods: Ten-week-old virgin Sprague-Dawley female rats were ovariectomized (OVX). The rats were administered via intragastric gavage 3 different doses of ICS (20, 50, or 100 mg·d-1) for 5 weeks. Their uterine weight and serum levels of 17β-estradiol (E2), follicle stimulating hormone (FSH) and luteinizing hormone (LH) were measured. The epithelial height, number of glands in the uterus, and number of osteoclasts in the femur were histologically quantified, and the expression of proliferating cell nuclear antigen (PCNA) was assessed immunohistochemically. Bone structural parameters, including bone mineral density (BMD), bone volume/tissue volume (BV/TV), trabecular thickness (Tb.Th) and trabecular separation (Tb.Sp) were measured using Micro-CT scanning. Results: Treatments of OVX rats with ICS (50 or 100 mg·kg-1·d-1) produced significant estrogenic effects on the uteruses, including the increases in uterine weight, epithelial height and gland number, as well as in the expression of the cell proliferation marker PCNA. The treatments changed the secretory profile of ovarian hormones and pituitary gonadotropins: serum E2 level was significantly increased, while serum LH and FSH levels were decreased compared with the vehicle-treated OVX rats. Furthermore, the treatments significantly attenuated the bone loss, increased BMD, BV/TV and Tb.Th and decreased Tb.Sp and the number of osteoclasts. Treatment of OVX rats with the positive control drug E2 (0.25 mg·kg-1·d-1) produced similar, but more prominent effects. Conclusion: ICS exhibits moderate estrogenic activities as compared to E2 in ovariectomized rats, suggesting the potential use of ICS for the treatment of menopausal symptoms and osteoporosis caused by estrogen deficiency. Keywords: chickpea; chickpea sprout isoflavone; phytoestrogen; 17β-estradiol; ovariectomized rat; uterine; follicle stimulating hormone; luteinizing hormone; osteoporosis This study was supported by the National Natural Science Foundation of China (81102474), the Guangdong Natural Science Foundation (S2011040003768), the Foundation of Guangzhou City Science and Technology Administration (2012J4300089), and the Foundation from Guangzhou Medical University (2011C09). * To whom correspondence should be addressed. E-mail yubolan@gmail.com (Bo-lan YU); hzhaof@mail.sysu.edu.cn (Zhao-feng HUANG) Received 2012-08-06 Accepted 2012-11-12